Being a good piano accompanist: issues and challenges/ Miyeko Jerikho Jordan Salingun - Jordan Salingun, Miyeko Jerikho (2014)
This study was carried out in March-May 2014 at the Faculty of Music UiTM, Shah Alam. This study focused especially on Bachelor Degree Music student piano accompanists from Music Education Department., Music Composition Department and Music Performance Department as well as experienced piano accompanists from outside UiTM. This study is based on responses from respondents regarding the issues and challenges of being a good piano accompanist. The main objectives of this study are: 1. To clarify what are the characteristics of a good piano accompanist. 2. To find out the problems and challenges often faced by piano accompanists. 3. To describe the differences in demands on piano accompanists between voice and instruments. This study conclude that student piano accompanists at Faculty of Music UiTM and experienced piano accompanists from outside UiTM faced similar issues and challenges to be a good piano accompanist. Though there are some similarities of the solutions, techniques and strategies applied in order to be a good piano accompanist, there are also a lot of other different ways which experienced piano accompanists used that can be helpful for student piano accompanists at Faculty of Music UiTM.